STUDI KOMPARASI PRESTASI BELAJAR PAI ANTARA SISWA AKTIVIS DAN NON AKTIVIS ROHIS - Bayu Ardiwansyah (AT-TAJDID, 2019)
This study aims to 1) find out the significance of the differences in PAI learning achievement between activist students and Spiritual non-visionary students in Accounting majors at SMKN 1 Metro 2) knowing the causes of differences in PAI learning achievement between activist students and non-religious Spiritual students in Accounting at SMKN 1 Metro. Rohis activist students referred to in this study are students who in addition to learning, they are also active in carrying out the activities of the Rohis organization. Whereas the non-religious Spiritual students referred to in this study were students who did not follow the Rohis organization. The results of the research at SMK Negeri 1 Metro, which researchers did to students Spiritual and Non-activist Rohis activists concluded that: 1) There are differences in learning achievement of Islamic Education between activist students and Non-Christian Spiritual Accounting Department at Metro 1 Vocational School. Where the learning achievements of Spiritual activist PAI students are better than the learning achievements of Rohan Nonaktivis students. The difference in learning achievement of Islamic Education between activist students and Spiritual Non-Service Students is significant, based on the results of t count = 4.630 consulted with t table (tt) at the significance level of 5% = 1.998 and at 1% significance level = 2.655. or 1,998 <4,630> 2,655. which means significant. 2) There are causes of differences in PAI learning achievements between activist students and non-religious Rohis students in the Accounting Department at SMK Negeri 1 Metro.Keywords: Activists, Non Activists, PAI Achievements, Comparative